Biocompatibility of Platinum Nanoparticles in Brain ex vivo Models in Physiological and Pathological Conditions - Gulino, Maurizio; Santos, Sofia Duque; Pêgo, Ana Paula (Frontiers in Neuroscience, 2021)
Platinum nanoparticles (PtNPs) have unique physico-chemical properties that led to their use in many branches of medicine. Recently, PtNPs gathered growing interest as delivery vectors for drugs, biosensors and as surface coating on chronically implanted biomedical devices for improving electrochemical properties. However, there are contradictory statements about their biocompatibility and impact on target organs such as the brain tissue, where these NPs are finding many applications. Furthermore, many of the reported studies are conducted in homeostasis conditions and, consequently, neglect the impact of the pathologic conditions on the tissue response. To expand our knowledge on the effects of PtNPs on neuronal and glial cells, we investigated the acute effects of monodisperse sodium citrate-coated PtNPs on rat organotypic hippocampal cultures in physiological or neuronal excitotoxic conditions induced by kainic acid (KA). The cellular responses of the PtNPs were evaluated through cytotoxic assays and confocal microscopy analysis. To mimic a pathologic scenario, 7-day organotypic hippocampal cultures were exposed to KA for 24 hours. Subsequently, PtNPs were added to each slice. We show that incubation of the slices with PtNPs for 24 hours, does not severely impact cell viability in normal conditions, with no significant differences when comparing the dentate gyrus (DG), as well as CA3 and CA1 pyramidal cell layers. Such effects are not exacerbated in KA-treated slices, where the presence of PtNPs does not cause additional neuronal PI uptake in CA3 and CA1 pyramidal cell layers. However, PtNPs cause microglial cell activation and morphological alterations in CA3 and DG regions indicating the establishment of an inflammatory reaction. Morphological analysis revealed that microglia acquire activated ameboid morphology with loss of ramifications, as a result of their response to PtNPs contact. Surprisingly, this effect is not increased in pathological conditions. Taken together, these results show that PtNPs cause microglia alterations in short-term studies. Additionally, there is no worsening of the tissue response in a neuropathological induced scenario. This work highlights the need of further research to allow for the safe use of PtNPs. Also, it supports the demand of the development of novel and more biocompatible NPs to be applied in the brain.